2022
DOI: 10.3389/fmed.2021.809312
|View full text |Cite
|
Sign up to set email alerts
|

The Torque Teno Virus Titer in Saliva Reflects the Level of Circulating CD4+ T Lymphocytes and HIV in Individuals Undergoing Antiretroviral Maintenance Therapy

Abstract: IntroductionTorque teno virus (TTV) is a non-pathogenic virus present in body fluids. Its titer in the circulation increases in association with immune suppression, such as in HIV-infected individuals. We evaluated if the TTV titer in saliva from HIV-positive individuals undergoing antiretroviral therapy (ART) was related to the circulating CD4+ T lymphocyte concentration and the HIV titer.MethodsSaliva was collected from 276 asymptomatic individuals undergoing ART, and an additional 48 individuals positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…In saliva, despite the extremely high mean of TTV viral load (49,542.83 copies/mL), one can observe a high standard deviation in which the great majority of the patients (percentile 75) also had much lower values (1,335.52 copies/mL) than those found in immunosuppressed patients with onco-haematological diseases (125,983 copies/mL) (25), chronic kidney disease (2,562.58 copies/ mL) (29) and HIV (501,187 copies/mL) (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In saliva, despite the extremely high mean of TTV viral load (49,542.83 copies/mL), one can observe a high standard deviation in which the great majority of the patients (percentile 75) also had much lower values (1,335.52 copies/mL) than those found in immunosuppressed patients with onco-haematological diseases (125,983 copies/mL) (25), chronic kidney disease (2,562.58 copies/ mL) (29) and HIV (501,187 copies/mL) (9).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown that Torque Teno Virus (TTV) is an endogenous marker of immune function, and consequently, the degree of immunosuppression in solid-organ-transplant patients ( 8 ). Both blood and saliva showed high viral loads of TTV in immunosuppressed individuals, in which assessment of saliva represents a non-invasive means of evaluating the immunological state of the patient ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence on the usefulness of TTV as a surrogate marker of the immune status in a variety of clinical scenarios ( Martin-Lopez et al, 2020 ; Honorato et al, 2021 ; Studenic et al, 2021 ), in particular SOT ( Fernandez-Ruiz et al, 2019 ; Redondo et al, 2022a ; Eldar-Yedidia et al, 2022 ; Jaksch et al, 2022 ), under the rationale that the T-cell-mediated immunity plays an instrumental role in controlling viral replication. Nevertheless, the relative contribution of the innate system—and its genetic determinants—has not been characterized so far.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, attention shifted from the pathogenic potential of TTV to its potential use as a biomarker. There is strong evidence supporting the use of TTV DNA-aemia as biomarker for monitoring the kinetics of functional immune competence before and after solid organ transplantation [ 15 17 ], monitoring the efficacy of antiviral treatments in HIV-infected patients [ 18 ], or even predicting clinical outcome in SARS-CoV-2-infected patients [ 19 ]. However, discriminating between TTV isolates that may be associated with pathology and innocuous isolates should not be overlooked, and genotyping and tracking their distribution thus remain an important task.…”
mentioning
confidence: 99%